2008
DOI: 10.1002/rcm.3869
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ionization tandem mass spectrometry fragmentation of protonated flavone and flavonol aglycones: a re‐examination

Abstract: Flavonoids are important phytochemicals which have been intensively studied in the last decades in view of their antioxidant activity, which is of particular importance in the case of flavones and flavonols, that differ in a single 3-OH group. Mass spectrometry has been used to elucidate the structures of many types of flavonoids and their metabolites. The work we present here is focused on the electrospray ionization tandem mass spectrometry (ESI-MS/MS) analysis of flavone and flavonols aglycones. Their fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 48 publications
3
46
0
Order By: Relevance
“…Hence, the similarity of UV and MS data did not allow to distinguish between the two isomers. Quercetin was finally assigned by a manual examination of the MS/MS spectrum, revealing a diagnostic product ion at m/z 219 [M+H-2C 2 H 2 O] + which was reported to be characteristic for quercetin only [20].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the similarity of UV and MS data did not allow to distinguish between the two isomers. Quercetin was finally assigned by a manual examination of the MS/MS spectrum, revealing a diagnostic product ion at m/z 219 [M+H-2C 2 H 2 O] + which was reported to be characteristic for quercetin only [20].…”
Section: Resultsmentioning
confidence: 99%
“…The product ions of the sodiated molecules (m/z values and relative abundances) are presented in [46][47][48][49][50][51][52] In order to determine the most probable protonation sites, the partial atomic charges for the neutral molecules, presented in Table 3, were computed using the Hamiltonean PM6 27 implemented in MOPAC2009. 28 The use of 20 According to the data presented in Table 3, for compounds 1, 2 and 3, the most probable protonation site will be the hydroxyl group linked to the C 4 atom of the sugar ring, whereas for compounds 4 and 5 the most probable site will be the sugar ring oxygen.…”
Section: Positive Ion Mode (Protonated and Sodiated Molecules)mentioning
confidence: 99%
“…These methodologies have been successfully employed in mass spectrometry studies, for example in the fragmentation study of flavonoids and flavonoid diglycosides using both ESI-MS and semi-empirical calculations. 20,21 and in the study of fullerene derivatives. 26 The fragmentation pathways are greatly influenced by the type of the precursor…”
mentioning
confidence: 99%
“…Those authors also reported that, although MALDI-MS allows the detection of slightly higher DPs than ESI-MS, better discrimination of the lower molecular ions (DP < 15) is observed in ESI-MS. Structural identification of flavonoids based on MS analysis has been object of many good articles that can be consulted for more detailed information (Ma et al, 1997(Ma et al, , 2001Justesen, 2000;Stobiecki, 2000;Cuyckens and Claeys, 2004;Abad-Garcia et al, 2009;Justino, Borges, and Florencio, 2009;Vukics and Guttman, 2010).…”
Section: Lc Coupled To Msmentioning
confidence: 99%